Burnout Syndrome in teachers: differences in education levels (Research, Society and Development, 2020)
This study aimed to analyze the difference in Burnout Syndrome dimensions in 1.284 teachers according to the different levels of teaching. A sociodemographic and labor data questionnaire and the Questionnaire for the Evaluation of Burnout Syndrome by the Work - CESQT-PE were used. The results, obtained through Analysis of Variance (ANOVA), revealed, in the kindergarten education, high averages in Illusion at Work and low in Psychological Wear and Indolence. Elementary and high school teachers presented low averages in the Illusion at Work dimension and high in Psychological Wear and Indolence, and elementary school teachers presented high guilt rates. The results indicate differentiated interventions according to each level of education.